2008
DOI: 10.1177/1473095208094822
|View full text |Cite
|
Sign up to set email alerts
|

The Minority-Race Planner in the Quest for a Just City

Abstract: This article reviews some basic concepts about planners' role in obtaining a just city, focusing in particular upon the possible role of racial minorities in the process of reaching such a city. We adopt Fainstein's two-part definition of what is 'valued' in a just city, and then discuss how planners who are racial minorities might be helpful for one part of that definition. Minority-race professionals may help bring tangible benefits to the workforce, but these benefits become difficult to cultivate if minori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Whiteness serves as a credential when public planning departments filter applications based on technical skills and graduate training program prestige (Tiarachristie, 2016). Harassing or pigeonholing of planners of color who do obtain jobs in such departments illustrates how formal nondiscrimination rules are decoupled from organizational practice (Thomas, 2008). These examples demonstrate Harris's (1993) theory that Whiteness functions as property that is protected by law.…”
Section: Racializationmentioning
confidence: 88%
See 2 more Smart Citations
“…Whiteness serves as a credential when public planning departments filter applications based on technical skills and graduate training program prestige (Tiarachristie, 2016). Harassing or pigeonholing of planners of color who do obtain jobs in such departments illustrates how formal nondiscrimination rules are decoupled from organizational practice (Thomas, 2008). These examples demonstrate Harris's (1993) theory that Whiteness functions as property that is protected by law.…”
Section: Racializationmentioning
confidence: 88%
“…The lack of capacity to think about, prioritize, and respond to racial equity limits departments' abilities to operationalize aspirational equity goals in ways that address specific disparities (Schrock et al, 2015). In addition, harassment and pigeonholing of planners of color stymie planners' abilities to advance social justice (Thomas, 2008). Departments' racialized rules and norms limit planners' abilities to pursue equity in the communities they serve.…”
Section: What Can Planners Do?mentioning
confidence: 99%
See 1 more Smart Citation
“…Although overtly racist tools used to discriminate in residential location, employment, unions, and schools are now illegal, barriers for poor and black residents remain and have become more subtle. For example, municipal fragmentation, exclusionary zoning, racial steering by real estate agents, and inadequate regional transportation continue to create significant barriers for black residents (Galster 2012;Thomas 2008). The 2008 recession exacerbated losses for black families as a result of unemployment and housing foreclosures.…”
Section: Detroit's Decline and Food System Impactsmentioning
confidence: 97%
“…For others, the skills that planners are able to employ place a burden of responsibility to contribute to public health (Laurian 2006) and mediation between community groups and local governments (Chaskin 2005;Padt and Luloff 2011). Thomas (2008) found that planners working with minority communities employed leadership in attempting to advance the participation and inclusion of their constituents in decision making. Forester's work takes this a little further.…”
Section: Leadership In Planningmentioning
confidence: 99%